2018
DOI: 10.1159/000489403
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Retinol-Binding Protein 4, N-Terminal proBNP and Renal Function in Older Patients Hospitalized for Heart Failure

Abstract: Background/Aim: Elevated plasma concentration of retinol-binding protein 4 (RBP4) has recently emerged as a potential new risk factor for cardiovascular diseases, including hypertension (HT) and coronary artery disease (CAD). Limited data suggest that RBP4 promotes inflammatory damage to cardiomyocytes and participates in the development of heart failure (HF). This study aimed to analyze the relationship between concentrations of plasma RBP4 and serum N-terminal proBNP (NT-proBNP), a powerful biomarker of left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The results are consistent with a previous study showing that serum RBP4 levels were increased in patients with advanced heart failure and remarkably decreased in response to mechanical unloading and hemodynamic correction after the implantation of left ventricular assist device . However, another study of elderly subjects found no significant differences of plasma RBP4 levels between subjects with low levels (<125 ng/mL) and high levels (≥125 ng/mL) of NT‐proBNP, as well as subjects with and without a history of hospitalization for heart failure . Moreover, no relationship was observed between the levels of RBP4 and NT‐proBNP in their study .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results are consistent with a previous study showing that serum RBP4 levels were increased in patients with advanced heart failure and remarkably decreased in response to mechanical unloading and hemodynamic correction after the implantation of left ventricular assist device . However, another study of elderly subjects found no significant differences of plasma RBP4 levels between subjects with low levels (<125 ng/mL) and high levels (≥125 ng/mL) of NT‐proBNP, as well as subjects with and without a history of hospitalization for heart failure . Moreover, no relationship was observed between the levels of RBP4 and NT‐proBNP in their study .…”
Section: Discussionsupporting
confidence: 90%
“…However, another study of elderly subjects found no significant differences of plasma RBP4 levels between subjects with low levels (<125 ng/mL) and high levels (≥125 ng/mL) of NT‐proBNP, as well as subjects with and without a history of hospitalization for heart failure . Moreover, no relationship was observed between the levels of RBP4 and NT‐proBNP in their study . The discrepancies might partly attribute to the heterogeneity in study design.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…RBP4, an adipokine which predominantly secreted by adipocytes, macrophages and hepatocytes, was first discovered in 2005 [105, 106]. Especially, RBP4 is produced by the visceral adipocytes under the status of obesity and insulin resistance.…”
Section: Adipokines Are Pathogenic Factors Which Link Psoriasis and Omentioning
confidence: 99%
“…Early diastolic dysfunction is usually characterized by decreased myocardial compliance and blocked diastolic filling ( 2 ). Late diastolic dysfunction is mainly manifested as congestive heart failure (HF) ( 3 ). DCM is one of the main complications of DM, differing from hypertension and other types of cardiovascular disease, which demonstrates one of the highest incidence rates of all cardiovascular diseases with an incidence rate of 16.9% in China ( 4 ).…”
Section: Introductionmentioning
confidence: 99%